2018
DOI: 10.1002/med.21555
|View full text |Cite
|
Sign up to set email alerts
|

Design of Hedgehog pathway inhibitors for cancer treatment

Abstract: Hedgehog (Hh) signaling is involved in the initiation and progression of various cancers and is essential for embryonic and postnatal development. This pathway remains in the quiescent state in adult tissues but gets activated upon inflammation and injuries. Inhibition of Hh signaling pathway using natural and synthetic compounds has provided an attractive approach for treating cancer and inflammatory diseases. While the majority of Hh pathway inhibitors target the transmembrane protein Smoothened (SMO), some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 167 publications
0
26
0
4
Order By: Relevance
“…[209] Hedgehog (Hh) signaling is responsible for pancreatic tumor initiation and progression as well as desmoplasia, which promotes both tumor growth and metastasis and hinders the delivery of chemotherapeutics. [210] Moreover, while upregulation of Hh in pancreatic cancer cells, the level of miR-let7b is downregulated. Kumar et al used mPEG-b-PCC-g-DC-g-TEPA lipopolymer to co-deliver miR-let7b and GDC-0449 which is a widely used Hh inhibitor and showed synergistic effect in pancreatic cancer cells (Capan-1, HPAF-II, T3M4, and MIA PaCa-2) and demonstrated that intratumoral administration of combination formulation into athymic nude mice bearing MIA PaCa-2 cells derived ectopic tumor significantly inhibited tumor growth.…”
Section: Lipopolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…[209] Hedgehog (Hh) signaling is responsible for pancreatic tumor initiation and progression as well as desmoplasia, which promotes both tumor growth and metastasis and hinders the delivery of chemotherapeutics. [210] Moreover, while upregulation of Hh in pancreatic cancer cells, the level of miR-let7b is downregulated. Kumar et al used mPEG-b-PCC-g-DC-g-TEPA lipopolymer to co-deliver miR-let7b and GDC-0449 which is a widely used Hh inhibitor and showed synergistic effect in pancreatic cancer cells (Capan-1, HPAF-II, T3M4, and MIA PaCa-2) and demonstrated that intratumoral administration of combination formulation into athymic nude mice bearing MIA PaCa-2 cells derived ectopic tumor significantly inhibited tumor growth.…”
Section: Lipopolymersmentioning
confidence: 99%
“…Hedgehog (Hh) signaling is responsible for pancreatic tumor initiation and progression as well as desmoplasia, which promotes both tumor growth and metastasis and hinders the delivery of chemotherapeutics . Moreover, while upregulation of Hh in pancreatic cancer cells, the level of miR‐let7b is downregulated.…”
Section: Nanocarriersmentioning
confidence: 99%
“…The Hedgehog (Hh) signaling pathway regulates cell growth and migration in developing embryo, and it is typically silent in adult tissues . Activation of Hh signaling pathway is initiated by Hh ligands bound to its receptor Patched (Ptch), which abrogates its repression of Smoothened (Smo) receptor . Smo then translocates to the primary cilia (PC) and initiates downstream Hh signaling, and the activated Gli proteins transfer into the nucleus to induce the expression of Hh target genes .…”
Section: Introductionmentioning
confidence: 99%
“…A LMA acomete indivíduos de todas as idades, mas a prevalência ocorre em indivíduos acima dos 60 anos de idade. O diagnóstico da LMA é realizado pela identificação de mieloblastos presentes no sangue periférico e medula óssea (Kumar et al, 2018;Löwenberg et al, 1999).…”
Section: Materiaisunclassified
“…Quando ocorre a desregulação da via, há uma proliferação celular descontrolada, resultando na tumorigênese, metastase celular e contribuindo ao fenótipo de resistência de múltiplas drogas (MDR) (Bariwal et al, 2018). Determinados oxisteróis poderiam exercer um papel importante como agente e/ou adjuvante antitumoral (Aupeix et al, 1995;Olkkonen et al, 2012).…”
Section: Via De Sinalização Hedgehog (Hh)unclassified